Anterograde Axonal Transport in Neuronal Homeostasis and Disease - Guillaud, Laurent; El-Agamy, Sara Emad; Otsuki, Miki; Terenzio, Marco (Frontiers in Molecular Neuroscience, 2020)
Neurons are highly polarized cells with an elongated axon that extends far away from the cell body. In order to maintain neuronal homeostasis, neurons rely extensively on axonal transport of membranous organelles and other molecular complexes. Axonal transport allows for spatio-temporal activation and modulation of numerous molecular cascades, thus playing a central role in the establishment of neuronal polarity, axonal growth and stabilization, and synapses formation. Anterograde and retrograde axonal transport are supported by various molecular motors, such as kinesins and dyneins, and a complex microtubule network. In this review, we will primarily discuss about the molecular mechanisms of anterograde transport pertinent to the elongation of the axonal compartment during the physiological development and maturation of neurons, to the establishment of functional synaptic connections. We will then provide an overview of the molecular and cellular perturbations that affect axonal transport and are often associated with axonal degeneration after injury and numerous neurological pathologies. Lastly, we will relate our current understanding of the role of axonal trafficking with other emerging cellular mechanisms, such as local translation and liquid phase separation.